Light-harvesting chlorophyll c-like pigment in Prochloron. - Larkum, A W (1994)
A chlorophyll c-like pigment, similar to magnesium-3,8-divinyl pheoporphyrin a5 monomethyl ester, has been isolated from Prochloron sp. obtained from five species of didemnid ascidians from the Great Barrier Reef, Australia, and from Palau, Micronesia. The pigment represents 4-15% of the total chlorophyll content and is shown to function in a light-harvesting pigment protein complex of Prochloron. The observation that all of the major chlorophylls (a+b+c) function in a light-harvesting role in Prochloron and possibly in other prochlorophytes is discussed in terms of the phylogeny of the prochlorophytes.